Responding to COVID-19 With the Aid of Mutually Beneficial Partnerships in Education - Biag, Manuelito; Gomez, Louis M.; Imig, David G.; Vasudeva, Ash (Frontiers in Education, 2021)
The COVID-19 pandemic has altered the structures and routines of K-12 education. Districts and school systems worldwide continue to adapt their ways of working to address a variety of challenges–many of whose dimensions are complex, dynamic, and not entirely known. Without cooperation and collaboration among stakeholders, institutions, and communities, we will be less able to address students’ social, emotional, and learning needs. In this paper, we present evidence that suggests mutually beneficial partnerships between local education agencies (LEAs) and institutions of higher education (IHEs), grounded in improvement science, can serve as an essential resource to address dilemmas brought about by the pandemic. We examine the work of four partnerships in the Improvement Leadership Education and Development (iLEAD) Network. Our analysis suggests that what matters in this period of uncertainty is that partnerships take a systems perspective, pay direct attention to the needs of critical users, avoid pre-determined programs and solutions, and engage in disciplined inquiry across institutional boundaries to affect positive and lasting change. A deeper understanding of how these partnerships operate–their principles, routines, methods, and tools–can help educational systems support students during the current global health crisis.